The conservatives since 1945 : the drivers of party change - Bale, Tim (Oxford University Press, 2016)
This text is about how and why parties in general, and the Conservative Party in particular, make changes to the face they present to the electorate, the way they organise themselves, and the policies they come up with. It is an in-depth but comprehensive study based on original archival sources.
Keywords: konservatiivipuolueet; konservatiivipuolueet : Iso-Britannia; puolueet : Iso-Britannia; poliittinen historia : Iso-Britannia